Can YKL-40 be used as a biomarker for interstitial lung disease?: A systematic review and meta-analysis. Issue 17 (30th April 2021) - Tong, Xiang; Ma, Yao; Liu, Tao; Li, Zhenzhen; Liu, Sitong; Wu, Guihui; Fan, Hong
Abstract: Background: Interstitial lung disease (ILD) has a poor prognosis and lacks specific biomarkers for early diagnosis, assessment of disease severity, and prognosis. YKL-40 levels were found to be elevated in patients with ILD, but these results are inconsistent. Therefore, we conducted a systematic review and meta-analysis to accurately study the relation between YKL-40 and ILD. Methods: We performed a systematic literature search in many databases (PubMed, Embase, the China National Knowledge Infrastructure, and Wanfang databases) and commercial Internet search engines to identify studies involving the role of YKL-40 in patients with ILD. The weighted mean difference with its 95% confidence interval were used to investigate the effect sizes. If obvious heterogeneity was found in the meta-analysis, the level of YKL-40 was directly compared by the Mann-Whitney test. Results: Sixteen eligible articles were finally identified. The results showed that the serum YKL-40 levels of patients with idiopathic pulmonary fibrosis, connective tissue-related ILD, sarcoidosis, cryptogenic tissue pneumonia, asbestosis-ILD, and idiopathic nonspecific interstitial pneumonia were higher than those in controls, but there was no increase in patients with pulmonary alveolar proteinosis. We also found that there are certain differences in the serum YKL-40 levels in patients with different types of ILD. The results showed that the bronchoalveolar lavage fluid YKL-40 levels of patients with idiopathic pulmonary fibrosis were significantly higher than that in controls. A systematic review indicated that there were correlations between the serum YKL-40 levels and lung function in patients with different ILD. In addition, YKL-40 may be used as a valuable biomarker for survival, with risk ratios ranging from 1.006 to 10.9. Conclusions: This study suggests that YKL-40 may be a useful biomarker for the diagnosis and prognosis of ILD.